Increased sensitivity of primary aniridia limbal stromal cells to travoprost, leading to elevated migration and MMP-9 protein levels, in vitro - Shuailin Li; Tanja Stachon; Shanhe Liu; Zhen Li; Shao-Lun Hsu; Swarnali Kundu; Fabian N. Fries; Berthold Seitz; Maryam Amini; Shweta Suiwal; Nóra Szentmáry (PLoS ONE, 2025)
Purpose In congenital aniridia, not only limbal epithelial cells but also limbal stromal cells may contribute to the development of aniridia associated keratopathy (AAK). Secondary glaucoma affects 50–75% of patients with congenital aniridia, and prostaglandin analogs are commonly used for conservative treatment. This study aimed to explore the effect of travoprost on corneal limbal stromal cells from healthy (LSCs) and congenital aniridia subjects (AN-LSCs), in vitro. Materials and methods Cells were extracted from aniridia (AN-LSCs) (n=7) and healthy donors (LSCs) (n=7). In culture, the cells were treated with travoprost at concentrations ranging from 0.039–40 μg/mL for 20 minutes. Cell viability, proliferation and migration were determined to assess the effect of travoprost on AN-LSCs and LSCs. Analysis of inflammation-, retinoic acid signaling-, and apoptosis-related genes and proteins was performed using qPCR, Western blot, and ELISA. One-way ANOVA was used to analyze cell viability and proliferation. The Mann–Whitney test was applied to compare between-group differences, while the Friedman test was used to assess within-group differences. Results Both in LSCs and AN-LSCs, travoprost treatment at 0.078 μg/mL and higher concentrations significantly reduced cell viability (p≤0.033; p<0.001) and proliferation decreased both in LSCs and AN-LSCs at 40 μg/mL travoprost concentration (p=0.006; p=0.002). At 6 and 12 hours, 0.313 μg/mL travoprost significantly increased the migration rate of AN-LSCs (p=0.021; p=0.021). AN-LSCs displayed lower PAX6 and JNK (MAPK8) mRNA (p<0.001) but higher MMP-3, MMP-9, ADH7, FABP5 and VEGFA mRNA levels (p≤0.037) than LSCs. PTGFR and JNK mRNA levels, MMP9 and ADH7 protein levels increased significantly in AN-LSCs after 0.313 μg/mL travoprost treatment (p≤0.039), while NF-κB and ADH7 protein levels decreased significantly in LSCs using 0.313 μg/mL travoprost (p=0.039; p<0.001). Conclusions Travoprost may affect viability, proliferation, and migration of both LSCs and AN-LSCs, with AN-LSCs exhibiting greater sensitivity than LSCs. Additionally, travoprost may regulate MMP-9 expression in AN-LSCs via the JNK signaling pathway. Furthermore, in AN-LSCs, travoprost treatment does not lead to a decrease in NF-κB and ADH7 protein levels.